The Use of Nearpod Media in the Social Sciences Subject at Islamic Elementary School - Rahmad Rahmad; Musdzalifah Oktaviany; Nur Inayah Syar (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
This study aims to describe whether there is an improvement in student learning outcomes after using Nearpod as a learning medium in the IPAS (Integrated Science and Social Studies) subject, specifically on electrical energy and technology in everyday life. This research employs a quantitative method with a Pre-Experimental Design. The population comprises all fifth-grade students at MIS Al-Jihad Palangka Raya, with Class VC selected as the sample using a purposive sampling technique. The instruments used include observation, pre-test, and post-test assessments. The instrument test was conducted in Class VIC, resulting in 21 valid items with a reliability coefficient of 0.873. Observations were carried out by directly assessing the learning process conducted by the fifth-grade teacher, using 17 observation indicators. The prerequisite tests included the normality test (0.407) and the homogeneity test (0.228). The study results showed that using Nearpod during classroom observation yielded a score of 95%, which falls into the very high category. The researchers measured the effectiveness of improving students' learning outcomes using the N-Gain score and obtained a value of 0.63, indicating moderate effectiveness. The t-test analysis produced a significance value of < 0.000. Based on the decision rule, since the significance value is less than 0.05, the researchers rejected the null hypothesis (H₀) and accepted the alternative hypothesis (Hₐ). Therefore, they concluded that the use of Nearpod had a significant effect on student learning outcomes.